(untitled) (Bioscience Journal, 2016)
Aureofuscin is an important tetraene macrolides antibiotic produced in submerged culture by Streptomyces aureofuscus isolated from the soil in China. In the present work, the effects of the addition of precursor on cell growth and the kinetics of aureofuscin production were investigated during submerged cultivation of Str. aureofuscus. The sodium acetate and sodium propionate are more suitable precursor than alcohol, sodium butyrate, n-propanol, n-butanol. The addition of acetate and propionic sodium at a ratio of 5:1 at a total concentration of 1.5mg mL−1 after 24 h showed stimulatory effects on aureofuscin production, reaching 3.708 mg mL−1 (approximately 267% increases in aureofuscin production, compared with the control culture). Moreover , A further enhancement in aureofuscin production was achieved by cultivation in a 5-L stirred-tank bioreactor under controlled pH conditions under the above optimum condition. The optimal fermentation conditions were that 4L/min ventilatory capacity, 220r/min rotational speed, dissolves oxygen not be lower than 20%, fermentation period 84h and pH should control nearby 5.5, and the maximum yield of aureofuscin of 3.99 mg mL−1 was achieved after 84 h When the sodium acetate and sodium propionate were added as a mixture of acetate and propionate at a ratio of 5:1 and a final concentration of 1.5 mg mL−1 after 24 h cultivation.